The Effect of Ownership Structure on Sustainability Reporting: The Moderating Role of Board Diversity - Ramahdani, Siska Putri; Tarmidi, Deden (LifeSciFi, 2025)
Sustainability reporting has emerged as a vital mechanism for demonstrating corporate accountability. However, many companies in Indonesia continue to disregard the environmental and social consequences of their operations despite the existence of regulatory requirements. This study investigates the influence of ownership structure on sustainability reporting disclosure, focusing on concentrated ownership, public ownership, and institutional ownership, with board diversity examined as a moderating factor. A quantitative approach was applied to 66 industrial sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023, using purposive sampling. Data were analyzed through multiple linear regression and Moderated Regression Analysis (MRA) with the Stata software. The results indicate that concentrated ownership positively and significantly affects sustainability reporting, whereas public and institutional ownership show negative effects. Furthermore, board diversity weakens the positive relationship between concentrated ownership and sustainability reporting, while strengthening the effects of public and institutional ownership. These findings demonstrate that ownership structure and board diversity jointly shape corporate transparency and accountability in sustainability reporting. The study concludes that enhancing gender diversity within boards can strengthen governance mechanisms, promote stakeholder trust, and encourage companies to adopt more comprehensive sustainability disclosure practices.